PEMBELAJARAN SASTRA ARAB (AL-ADAB AL-‘ARABÎ) - Rosyidi, Choir; Setyabudi, Mohammad Arif (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
This article examines matters related to learningArabic literature. Literature (al-Adab) is the delivery ofsomething with a deep feeling processing laden and artisticvalue of the picture will be given and expressed in particularwith the rules of a particular way. Periodic of literaturebegan in the period of ignorance, Islamic period whichincludes Daulah Umayyah, Abbasiyah period continued, theOttoman Empire, and finally the modern period. While thepurpose of teaching literature in between to increasestudents' knowledge and understanding of literature to lifemore purposeful and be good; also helps studentsunderstand the social inequalities in life and also to play arole to solve it. Learning methods such literature is threefold:historical method, the method of literary art, and the methodof thematic literature. While the technique of deliveringdifferentiated materials at a basic level, intermediate, andadvanced. Furthermore, the ability to feel the beauty ofArabic literature is not obtained by simply mastering therules of the Arabic language, but with a lot of reading goodliterature and tried to explore the beauty-beauty